Aplikace manažerské etiky v zásobování ČD, a. s. - Vobořil, Zbyněk (Univerzita Pardubice, 2006)
Práce pojednává o aplikaci manažerské etiky v oblasti zásobování ČD, a.s. Bakalářská práce zahrnuje předmluvu, úvod a osm kapitol včetně závěru. Kapitoli jsou rozděleny do dvou skupin, a to teoretické a praktické části. V teoretické části je uvedena manažerská etika, etika jako část managementu a základní terminologie používaná v manažerské etice. V praktické části je uvedena charakteristika a analýza současného stavu v zásobování ČD, a. s., pomocí dotazníku, možné návrhy a opatření a vyhodnocení a přínos navržených opatření.

This bachelor work deal with aplication of business ethics at logistic ČD, a.s. Bachelor work contains an preface, introduction and eight chapters inclusive of conclusion. The chapters are divided into two sections - theoretical and practical section. The theoretical part is chapter managerial ethics, ethics as the part of management and basic terminology in managerial ethics. The practical part is chapter characterization and analysis of the present condition of supply ČD, a. s., by quastionnaire, possible proposals and measures and evaluation and contribution of proposed measures.
Aplication of business ethics at logistic ČD, a.s.
Keywords: ethics; business ethics; aplication; logistic; Czech Railways; etika; manažerská etika; aplikace; Zásobování; České dráhy